MODELLING THE TRANSMISSION DYNAMICS OF COVID-19 INFECTION WITH VACCINATION, QUARANTINE, TREATMENT AND PUBLIC CAMPAIGN INTERVENTIONS - Yusuf Emmanuel; Jacob Hyellachari Maspalma; Song, I. M.; Bade, S. H.; Abubakar, A.; Umar Gidado; Tarfa, F. S. (FUDMA JOURNAL OF SCIENCES, 2025)
Coronavirus disease (COVID-19) is an infectious illness caused by a novel coronavirus that emerged in Wuhan, China, in late 2019. While most infected individuals experience mild to moderate respiratory symptoms and recover without intensive medical intervention, the rapid spread of the virus has presented significant global health challenges. This study develops and analyzes a deterministic compartmental model for the transmission dynamics of COVID-19, incorporating vaccination, public awareness campaigns, and natural death. The model consists of seven compartments and examines the effects of both pharmaceutical and non-pharmaceutical interventions. Key mathematical analyses include the positivity and invariance of solutions, determination of disease-free and endemic equilibria, computation of the basic reproduction number, and stability analysis of the disease-free equilibrium. Sensitivity analysis and numerical simulations reveal that a combined strategy involving vaccination and quarantine is highly effective in controlling the spread of the disease. Based on the findings, it is recommended that phased implementation of vaccination and sustained public health interventions be emphasized to mitigate and ultimately eliminate COVID-19 transmission.